Analysis Planning Relay Layout with Computerized Relative Allocation of Facilities Technique Approach - Marcelani, Rigel Saesaria; Joumil Aidil SZS; Yekti Condro Winursito (Newinera Publisher, 2024)
PT XYZ is one of the manufacturing industries engaged in the production of palm oil processing. The products produced are cooking oil and margarine. So far, the implementation of activities has been hampered by the current layout conditions having a less efficient material handling path length, in addition, the distance between facilities is too far ± 150m which results in repeated transportation, this results in PT XYZ's material transfer activities being less effective. Therefore, this study aims to redesign the layout of production facilities in order to minimize material handling costs and raw material movement distances to be more effective. From these problems, the method used is the CRAFT (Computerized Relative Allocation of Facilities Techniques) method, this method can be done with the help of FTC (From to Chart), ARC (Activity Relation Chart) and ARD (Activity Relationship Diagram) calculations. The results of this study showed that the CRAFT algorithm succeeded in saving total material handling costs of Rp. 469,352.04 per day and reducing the total distance of movement by 67.15 meters. The reduction in material handling costs achieved was Rp 2,114,734.77 or around 81.84%, while the reduction in material handling distance reached 306.85 meters or around 82.05%.